Relationship of Testosterone, LH, Estradiol, IGF-1, and SHBG with Physical Performance of Master Athletes - Santos, Patrick Anderson; da Silva Aguiar, Samuel; Barbosa, Lucas Duarte Maciel Pinheiro Freire; dos Santos Rosa, Thiago; Sales, Marcelo Magalhães; Maciel, Larissa Alves; Lopes de Araújo Leite, Patrício; Gutierrez, Sara Duarte; Minuzzi, Luciele Guerra [UNESP]; Sousa, Caio Victor; Lewis, John Eugene; Simões, Herbert Gustavo (Taylor & Francis, 2024)
Purpose: The aim of this study was to investigate and compare the levels of luteinizing hormone (LH), testosterone (T), estradiol (ES), sex hormone-binding globulin (SHBG), and insulin-like growth factor 1 (IGF-1) in master sprint (MS) and master endurance (ME) athletes. Additionally, the possible associations between these hormones, body composition, and lipid profile with athletic performance (% of performance in relation to the current world record) were analyzed. Materials andMethods: The participants were all men: (i) 34 MS (51.0 ± 6.8 years); and (ii) 32 ME (51.7 ± 9.4 years). Student’s t-tests for independent samples were performed to compare all variables between groups. Results: MS had a significantly higher (p =.008) average IGF-1 (154.78 ± 29.85 ng/mL) when compared to ME (129.92 ± 25.48 ng/mL). Performance was significantly correlated with IGF-1 (r = 0.424). The MS group had a moderately lower body fat than ME athletes (MS 12.54 ± 4.07 vs. ME 14.60 ± 4.12; p =.078; d = 0.503). Conclusions: Thus, strength/power training exercise/sport seems to be more beneficial for obtaining a higher IGF-1 compared to aerobic/distance exercise/sport. In addition, LH, T, ES, and SHBG were similar between the two groups of athletes and were comparable to the reference values of younger adults.
Keywords: Hormonal profile; performance; running; sprinting; track and field